Fighting the Antibiotic Crisis: Flavonoids as Promising Antibacterial Drugs Against Helicobacter pylori Infection - González, Andrés; Casado, Javier; Lanas, Ángel (Frontiers in Cellular and Infection Microbiology, 2021)
Over half of the world’s population is estimated to be infected with Helicobacter pylori. Chronic infection with this microbial class I carcinogen is considered the most important risk factor for developing gastric cancer. The increasing antimicrobial resistance to first-line antibiotics mainly causes the failure of current eradication therapies, inducing refractory infections. The alarming increase in multidrug resistance in H. pylori isolates worldwide is already beginning to limit the efficacy of existing treatments. Consequently, the World Health Organization (WHO) has included H. pylori in its list of “priority pathogens” for which new antibiotics are urgently needed. Novel strategies must be followed to fight this antibiotic crisis, including properly exploiting the proven therapeutic potential of medicinal plants and plant-derived phytochemicals. In this mini-review, we overview the impressive properties of naturally occurring flavonoids as effective antimicrobial agents against H. pylori, which support the use of these plant-derived bioactive compounds as promising drug candidates for inclusion in novel and personalized combinatory therapies against H. pylori infection.